Assessment of the Characteristics of interpersonal communication competence among postgraduate students from different cultures - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab; Mohamad Hilmi, Mat Said; Nor Ashikin, Abdul Aziz (Immigrant Institute, Sweden, 2018)
This study was carried out to assess the characteristics of interpersonal communication competence among postgraduate students from different cultures at a Malaysian public university. This study applied the mixed methods research design with the participation of 130 postgraduate students from 18 different countries. The Interpersonal Competence Questionnaire (ICQ) was used as the main instrument of this study. Based on the results from this study, their interactions with their peers from different cultures helped the participants to improve the contact initiation, disclosure and conflict management skills of their interpersonal communication competence and gain some new personal and cultural skills and information. However, the participants were struggling to learn how to manage probable conflicts during their interactions with their peers from different cultures. The results from this study illustrate that the level of education variable affect interactions among individuals from different cultures in the Asian context of communication.